2015
DOI: 10.1088/2041-8205/808/2/l45
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependence of Polarization of Zebra Pattern in Type-Iv Solar Radio Bursts

Abstract: We investigated the polarization characteristics of a zebra pattern (ZP) in a type-IV solar radio burst observed with AMATERAS on 2011 June 21 for the purpose of evaluating the generation processes of ZPs. Analyzing highly resolved spectral and polarization data revealed the frequency dependence of the degree of circular polarization and the delay between two polarized components for the first time. The degree of circular polarization was 50-70 % right-handed and it varied little as a function of frequency. Cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…See Kaneda et al (2015) for a discussion of the frequency dependences of the polarization characteristics of a ZP event.…”
Section: Overview Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…See Kaneda et al (2015) for a discussion of the frequency dependences of the polarization characteristics of a ZP event.…”
Section: Overview Of the Resultsmentioning
confidence: 99%
“…Melrose (2006) also considered depolarization due to reflection at sharp density boundaries. Kaneda et al (2015) investigated the circumstances under which such depolarization processes occur by analyzing the frequency dependence of the delay between the two circularly polarized components. Based on their results, they suggested that depolarization occurs very close to the emission source, where the difference between the group velocities of the two circular wave modes is relatively large.…”
mentioning
confidence: 99%
“…Likewise, we did not consider the possible evolution of the ZP emission polarisation (e.g. Zlotnik et al 2014;Kaneda et al 2015). Accounting for these effects may provide us with additional seismological information, and hence should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there was a strong correlation between the growth rate and peak flux of the bursts. Kaneda et al (2015) investigated the polarization characteristics of a zebra pattern in a type-IV solar radio burst observed with AMATERAS. Cross-correlation analysis determined that the left-handed circularly polarized component was delayed by 5070 ms relative to the right-handed component over the entire frequency range of the zebra pattern.…”
Section: Division E Commission 49mentioning
confidence: 99%
“…Cross-correlation analysis determined that the left-handed circularly polarized component was delayed by 5070 ms relative to the right-handed component over the entire frequency range of the zebra pattern. Katoh et al (2014) investigated the fine spectral structures included in a type IV burst observed by AMATERAS, and proposed a generation model that suggests wave-wave coupling between Langmuir waves and whistler-mode chorus emissions generated in a post-flare loop. This was inferred from the similarities in the plasma environments of a post-flare loop and the equatorial region of Earth's inner magnetosphere.…”
Section: Division E Commission 49mentioning
confidence: 99%